The Utilization of Various Types of Organic Fertilizer and Trichoderma on Increasing the Production and Quality of Chryshone Cut Flowers - A.A. Sagung Putri Risa Andriani; Arjana, Gusti Made; Sang Ayu Made Putri Suryani; I Gusti Ayu Dewi Seri Rejeki; Sunadra, I Ketut (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2022)
Horticultural commodities, especially ornamental plants, have high economic value in the market. It is necessary to research the introduction of appropriate technology in increasing the intensity of chrysanthemum cultivation such as the use of domestically created organic fertilizers and Trichoderma, which are formulated with local resources in chrysanthemums to improve quality and added value and utilize the potential of agricultural resources that are easy to apply following the ability of farmers and have a real impact on increasing income. The purpose of this research is to obtain a package of organic matter and Trichoderma that is suitable for the agro-climate, thus farmers will be interested in adopting the technology and developing it widely into their production system. The method used is field research in a greenhouse using a factorial randomized block design, with two factors that will be used to achieve the goal, namely the use of various types of organic fertilizers and the administration of Trichoderma doses. If the single treatment has a significant or very significant effect, then continue with the 5% BNT average value test, whereas if there is an interaction between the two factors, it is tested with Duncan't 5%. Based on the results of the study, all types of organic fertilizers, namely organic cow manure, organic pig manure, and organic goat manure combined with Trichoderma were able to suppress rust disease in chrysanthemums and increase the production and quality of chrysanthemums. Goat dung fertilizer and a dose of 5 tons-¹ ha of Trichoderma tended to produce flower stalk height, flower stalk weight, stem diameter, flower diameter, economical flower fresh weight and resulted in the lowest percentage of leaves affected by rust disease.